Incidental pathologies in appendectomy specimens - An interesting series of cases in a tertiary care center in Eastern India - Sanghamitra Mukherjee; Debajyoti Singha Roy; Vandana Maroo; Meghadipa Mandal (Asian Journal of Medical Sciences, 2023)
Acute appendicitis is the most common surgical emergency worldwide, with appendix being the most frequently encountered specimen by a reporting histopathologist. They may sometimes show rare and uncommon histomorphologic pictures that may create diagnostic dilemmas, few of such cases being discussed here. There are two cases of appendicular neuroendocrine tumors (NETs) that initially presented as acute appendicitis clinically, with microscopic tumor foci measuring <1 cm each. Immunohistochemistry for synaptophysin substantiated the histopathological diagnosis in one case. Neurogenic appendicopathy is another non-neoplastic entity discussed that may be overdiagnosed as appendicular neoplasms such as NET, neuromas, or neurofibromas. Granulomatous appendicitis may be another cause of recurrent appendicitis due to a variety of cases, tuberculosis being one of them and antitubercular therapy being the mainstay of treatment for these cases. Xanthogranulomatous appendicitis may simulate colonic malignancy, Crohn’s disease, malakoplakia, etc. Histopathological features are the main diagnostic modalities for these instances. Pinworm is a common helminthic infection of the gastrointestinal tract. Currently, its incidence is on the declining side due to better sanitation practices. However, it must be reported in appendectomy sections, if present, to initiate a course of antihelminthic drugs. Pseudomyxoma peritonei is an uncommon entity classically characterized by mucinous ascites resulting from ruptured appendiceal mucinous tumors, one such rare case being reported here. Low-grade appendiceal mucinous neoplasm is a distinctive entity rarely seen in appendectomy cases, belonging to groups of appendiceal mucinous neoplasms. One such instance has been depicted here.